A Patient With a Noninvasive Mucinous Ovarian Borderline Tumor Presenting With Late Pleural Metastases. (March 2015) - Simons, Michiel; Nagtegaal, Iris D.; Overbeek, Lucy I.; Flucke, Uta; Massuger, Leon F.; Bulten, Johan
Abstract : We describe a patient diagnosed with a noninvasive intestinal-type mucinous ovarian borderline tumor presenting with pleural metastases 4 yr later. This was confirmed by an identical mutation in TP53 in both tumors. Metastases of ovarian borderline tumors outside the pelvis or abdominal cavity are extremely rare. A large epidemiologic search in the Dutch Pathology Registry that was conducted in support of this case, identifying 1812 intestinal-type mucinous ovarian borderline tumors, suggests that microinvasion is associated with a higher risk of disease spread. Our case illustrates that intestinal-type mucinous ovarian borderline tumor with intraepithelial carcinoma might also have a higher risk of metastasis, assuming that microinvasion occurs in the presence of intraepithelial carcinoma. Both intraepithelial carcinoma and microinvasion could be a trigger for more extensive tumor sampling to prevent sampling error of (micro)invasive adenocarcinoma. In addition, this case draws attention to the developmental spectrum of Types I and II ovarian carcinomas. Borderline tumors harboring a TP53 mutation require further studying to examine whether they might develop into high-grade Type II carcinomas.